ECONOMIC AND LEGAL BASIS OF PROTECTION OF BUSINESS ACTIVITY FROM CORRUPTION CRIME - Makhmudova Sayyora; Kabilova Kamola (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
The article analyzes and substantiates the economic and legal basis of protecting business activity from corruption.